Structure elucidation and in vitro rat intestinal fermentation properties of a novel sulfated glucogalactan from Porphyra haitanensis - Peilin Chen; Lu Liu; Zirun Cheng; Yi Zhang; Baodong Zheng; Xiaoke Hu; Hongliang Zeng (Food Science and Human Wellness)
This study was to investigate the structure and rat fecal microbial fermentation properties of a polysaccharide fraction (PHP2) isolated from the red marine alga Porphyra haitanensis. PHP2 was characterized as a sulfated glucogalactan, with a hypothetical backbone structure of →4)Gα(1→6)G4Sβ(1→4)Glc(1→ and a side chain of Man(1→6)Glc. PHP2 had an irregular spherical chain conformation. The 16S rRNA sequence analysis revealed that PHP2 modulated the rat fecal micro-flora composition, with a similar effect to inulin, changing the dominant genus (Lactobacillus and Escherichia-Shigella) and promoting the growth of organisms that degrade sulfur-containing polysaccharides, such as Desulfovibrio, Ruminococcaceae_UCG-005, and Ruminococcus_2. PHP2 can promote production of acetic, propionic and butyric acid by rat fecal micro-flora. Prediction of metabolic function suggested that PHP2 could modulate cholesterol metabolism. The sulfated glucogalactan fermentation behavior may be associated with its monosaccharide composition, chain branching and chain conformation. PHP2 appeared to have considerable potential as functional food, and was associated with sulfur-containing polysaccharides in general.